Private school teachers' perception of organizational commitment in Klang Valley, Malaysia - Ng, Pek Cheng; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The main purpose of this study is to determine the level of organizational commitment among private school teachers in Klang Valley. Survey questionnaires were distributed to five private schools. 110 private school teachers participated in the survey. Data regarding organizational commitment were analyzed by using IBM SPSS Software version 22.0. Descriptive statistic was employed to identify level of teachers' organizational commitment. The result revealed that the level of organizational commitment are moderate.